Analysis Teachers' Strategies in Teaching Vocabulary at SMAN 2 Luwuk - Abdul Rabbi Arrasul; Desriani Nggolaon; Desi Rita Natalis Pinaling (English Education Study Program, 2023)
Vocabulary is a component of language skills, besides that vocabulary is the basis of how students can speak, listen, read, and write. Therefore, the teacher is required to carry out learning and teaching vocabulary creatively, so it becomes more meaningful to attract students' interest to learn it. The purpose of this research is to figure out the teachers’ strategies in teaching vocabulary at SMAN 2 Luwuk and the importance of the strategies in helping the English teachers in teaching vocabulary at SMAN 2 Luwuk. In this research, the researcher used a qualitative method with descriptive research design to address this issue. In collecting data, the researcher used two instruments: observation and interview. In analyzing the data, the researcher used several techniques: (1) data collection, (2) data reduction, (3) drawing conclusion. Subjects in this research are English teachers at SMAN 2 Luwuk. Based on observation and interview the researcher found the teachers’ strategies in teaching vocabulary: using translation, using picture, word list, memorization, gesture, repetition, and mixing jokes. In teaching vocabulary, these strategies are very important for teachers. In conclusion, these strategies really help English teachers at SMAN 2 Luwuk to make learning becomes faster, easier, more enjoyable, and more effective.